Adsorption Study for the Removal of Nitrate from Water Using Local Clay - A. Battas; A. El Gaidoumi; A. Ksakas; A. Kherbeche (The Scientific World Journal)
Our research aimed at the removal of nitrate ions through adsorption by local clay. A series of batch experiments were conducted to examine the effects of contact time, adsorbent characteristics, initial concentration of nitrate, pH of the solution, concentration, and granulometry of adsorbent. Adsorption isotherms studies indicated that local clay satisfies Freundlich’s model. The rate of reaction follows pseudo-second-order kinetics. Local clay successfully adsorbs nitrates at pH acid. The adsorption capacity under optimal conditions was found to be 5.1 mg/g. The adsorption yield increases with adsorbent dose and decrease with initial concentration of nitrate. The local clay was characterized by the X-ray fluorescence method (XRF), X-ray diffraction (XRD), Fourier transform-infrared spectroscopy (FTIR), scanning electronics microscopy (SEM), and measurement of specific surface area (BET). The results of the study indicated that local clay is useful materials for the removal of nitrates from aqueous solutions which can be used in water treatment without any chemical modification.